AtBBX21 and COP1 genetically interact in the regulation of shade avoidance - Crocco, Carlos Daniel (2010)
Plants grown at high densities perceive the reduction in the ratio of red (R) to far-red (FR) light as a warning of competition. This light signal triggers morphological responses such as hypocotyl and stem elongation, and acceleration of flowering, which are known collectively as the shade-avoidance syndrome (SAS). Mutations in the photomorphogenic repressor COP1 suppress the SAS, but how COP1 modulates these responses is uncertain. We identified a new mutant with altered responses to natural shade, named lhus (long hypocotyl under shade). lhus seedlings have longer hypocotyls than wild-type under a low R:FR ratio, but not under sunlight or darkness. The lhus phenotype is due to a mutation affecting a B-box zinc finger transcription factor encoded by At1g75540, a gene previously reported as AtBBX21 that interacts with COP1 to control de-etiolation. Mutations in genes encoding other members of this protein family also result in impaired SAS regulation. Under short-term canopy shade, LHUS/BBX21 acts as positive regulator of SAS genes such as PAR1, HFR1, PIL1 and ATHB2. In contrast, global expression analysis of wild-type and lhus/bbx21 seedlings revealed that a large number of genes involved in hormonal signalling pathways are negatively regulated by LHUS/BBX21 in response to long-term canopy shade, and this observation fits well with the phenotype of lhus/bbx21 seedlings grown under a low R:FR ratio. Moreover, the bbx21 bbx22 double mutation restored the SAS in the cop1 background. We propose that LHUS/BBX21 and other B-box-containing proteins, such as BBX22, act downstream of COP1, and play a central role in early and long-term adjustment of the SAS in natural environments. © 2010 Blackwell Publishing Ltd.